The impact of uncertainty in black carbon's refractive index on simulated optical depth and radiative forcing - Digby, Ruth A. R.; von Salzen, Knut; Monahan, Adam H.; Gillett, Nathan P.; Li, Jiangnan (Atmospheric chemistry and physics, 2025)
The radiative forcing of black carbon (BC) is subject to many complex, interconnected sources of uncertainty. Here we isolate the role of the refractive index, which determines the extent to which BC absorbs and scatters radiation. We compare four refractive index schemes: three that are commonly used in Earth system models and a fourth more recent estimate with higher absorption. With other parameterizations held constant, changing BC's spectrally varying refractive index from the least- to most-absorbing estimate commonly used in Earth system models (m550 nm=1.75–0.44i to m550 nm=1.95–0.79i) increases simulated absorbing aerosol optical depth (AAOD) by 42 % and the effective radiative forcing from BC–radiation interactions (BC ERFari) by 47 %. The more recent estimate, m532 nm=1.48–0.84i, increases AAOD and BC ERFari by 59 % and 100 % respectively relative to the low-absorption case. The AAOD increases are comparable to those from recent updates to aerosol emission inventories and, in BC source regions, up to two-thirds as large as the difference in AAOD retrieved from MISR (Multi-angle Imaging SpectroRadiometer) and POLDER-GRASP (Polarization and Directionality of the Earth's Reflectances instrument with the Generalized Retrieval of Atmosphere and Surface Properties algorithm) satellites. The BC ERFari increases are comparable to previous assessments of overall uncertainties in BC ERFari, even though this source of uncertainty is typically overlooked. Although model sensitivity to the choice of BC refractive index is known to be modulated by other parameterization choices, our results highlight the importance of considering refractive index diversity in model intercomparison projects.